The Correlation Between Personality, Self-Confidence and English Achievement of Year Ten Students MAN 1 Makassar - Hardianti, Hardianti; Jabu, Baso; Sakkir, Geminastiti (Journal of Excellence in English Language Education, 2023)
This study discussed students’ personality, self-confidence, and English achievement. The research was conducted to determine: (1) the students’ personality. (2) the students’ self-confidence. (3) the students’ English achievement. (4) the correlation between personality and English achievement. (5) the correlation between self-confidence and English achievement. There are 405 students in year ten as a population that is divided into 11 classes, the writer took 37 students as samples that are taken from one class. The technique of collecting the data was cluster random sampling. In collecting the data, the researcher used two questionnaires and a test. The first questionnaire was a self-confidence questionnaire, the second was The Myers-Briggs Type Indicator (MBTI) a personality questionnaire that assists a person in identifying some significant personal preferences used to determine the personality type, and the last was the English test which used TOEFL junior test. The data then were analyzed using descriptive statistics and Pearson Product Moment Correlation Coefficient in SPSS version 23. The results showed that: (1) the noticeable majority of first-grade students were introverted, Intuition, Thinking, Judgers and INTJ types showed higher in the class. (2) The self-confidence of the students was categorized into high enough levels. (3) Students’ English achievement was categorized into average level. (4) There was no significant correlation between personality and student’s English achievement. (5) There was a significant correlation between students’ self-confidence and English achievement with r = 0.597 classified into a fair category. The higher the self-confidence, English achievement would be higher.